Rapunzel - Southgate, vera (London : Lady Bird Ltd)
There the once was a man and woman, who both really wanted a child, but did not have one. The wife became very sick, and wanted rampion to cure her, but it was only found in the witches garden. She sent her husband to get her some, and he eventually got caught. The witch made him promise that they would give their first child up, so that the witch could raise her - in return they could have all the rampion they wanted. Rapunzel was born, given to the witch, where she became a beautiful young women with long locks of blonde hair. The witch wanted to protect her from the world, so she locked her in a castle, with only a window. The witch would visit everyday and would call up to Rapunzel, "Rapunzel, Rapunzel, let down your golden hair," where she would reluctantly do so. Eventually a Prince heard her signing from the window, and fell in love. He proceeded to watch the witch, and did the same thing himself. Once he got to Rapunzel, they instantly fell in love and wanted to get married. After multiple visits from the prince, Rapunzel eventually slipped and accidentally mentioned the Prince visiting. The witch cut her hair off, and sent her to live in solitude. When the prince came for Rapunzel, the witch let the hair down and he came up to a surprise. The Prince jumped from the window, fell into a bush, and became blind. After years of wandering the forest, Rapunzel and the Prince found each other. Her tears of happiness cured his blindness and they lived happily ever after together in the kingdom.
English Fiction Book
Keywords: English - Fiction Book